Penerapan Green Accounting Berbasis University Social Responsibility - Rachmadhani, Susy; Suhartini, Dwi (Akuisisi : Jurnal Akuntansi, 2023)
This study aimed to determine whether there were differences in USR-based green accounting practices at the University of 17 August 1945 Surabaya and The University of Dynamics Surabaya. This quantitative study uses the Independent Sample T-test in hypothesis testing with the SPSS 25 analysis tool. This study used primary data by spreading questionnaires. Samples are determined using the purposive sampling method with certain criteria. The number of samples obtained was 63 respondents. The results showed that both universities had a high level of commitment related to environmental concerns, especially in issuing policies regarding the environment. However, the two universities have not been optimally involved in environmental issues, in making reports on the allocation of special costs for the environment, and implementing environmental audits.